2012
DOI: 10.1016/j.rasd.2011.06.005
|View full text |Cite
|
Sign up to set email alerts
|

An examination of challenging behaviors in autistic disorder versus pervasive developmental disorder not otherwise specified: Significant differences and gender effects

Abstract: Children with Autism Spectrum Disorders (ASDs) are well-known for engagement in challenging behaviors. Unfortunately, due to its absence as a criterion for diagnosis in the DSM-IV-TR, little attention has been paid to the endorsement rates of such behaviors. However, a recently developed measure to assist in the diagnosis of infants and toddlers with autism and PDD-NOSthe Baby and Infant Screen for Children with aUtIsm Traits (BISCUIT)has included a section designated for just this reason. This study used the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 116 publications
(262 reference statements)
1
16
0
Order By: Relevance
“…If this heightened occurrence of challenging behaviors is found in the young child with ASD, it will support researchers who have noted that individuals with ASD are at an increased risk for engaging in challenging behaviors at a high rate (Holden and Gitlesen 2006;Lecavalier 2006;Matson and Shoemaker 2009;Murphy et al 2005;Sturmey et al 2008). Furthermore, it would add support to the emerging literature which indicates that these behavioral problems are distinct from those with other delays and can be detected very early in life (Kozlowski and Matson 2010;Matson et al 2009b). This outcome would, thus, point to the importance of early detection of challenging behaviors in those with ASD and subsequent early, intensive intervention.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…If this heightened occurrence of challenging behaviors is found in the young child with ASD, it will support researchers who have noted that individuals with ASD are at an increased risk for engaging in challenging behaviors at a high rate (Holden and Gitlesen 2006;Lecavalier 2006;Matson and Shoemaker 2009;Murphy et al 2005;Sturmey et al 2008). Furthermore, it would add support to the emerging literature which indicates that these behavioral problems are distinct from those with other delays and can be detected very early in life (Kozlowski and Matson 2010;Matson et al 2009b). This outcome would, thus, point to the importance of early detection of challenging behaviors in those with ASD and subsequent early, intensive intervention.…”
mentioning
confidence: 54%
“…The 2-year-old children diagnosed with ASD showed a higher level of stereotypy than their typically developing 2-year-old counterparts during assessment conditions, and this gap incrementally increased at ages 3 and 4 years. Likewise, Kozlowski and Matson (2010) found that toddlers between the ages of 17-37 months who had ASD engaged in significantly more challenging behaviors than atypically developing, matched peers. Furthermore, significant differences were detected with respect to specific forms of aggressive, self-injurious, and stereotypic behaviors across diagnostic groups.…”
mentioning
confidence: 95%
“…In early years TD males are more likely to have delayed first words, have a smaller vocabulary and less grammatically complex sentences (Eriksson et al 2012;Bouchard et al 2009). This finding has more recently been replicated in an ASD population (Kozlowski and Matson 2012). In male TD populations, structural language skills (vocabulary and sentence grammar) are thought to catch up with females by mid-childhood, although females are likely to demonstrate better pragmatic skills (i.e.…”
Section: Introductionmentioning
confidence: 81%
“…Parents of children with autism spectrum disorder (ASD) report higher levels of stress and other negative affective states than parents of typically developing children [Baker-Ericzen, Bookman-Frazee, & Stahmer, 2005;Dyson, 1993;Eisenhower, Baker, & Blacher, 2005;Montes & Halterman, 2007] or parents of children with other developmental disorders [Boyd, 2002;Kozlowski & Matson, 2012;Sanders & Morgan, 1997]. Stress places all family members at increased risk for psychosocial problems including reduced well-being and increased depressive symptoms [Ingersoll & Hambrick, 2011;Paynter, Riley, Beamish, Davies, & Milford, 2013;Rivard, Terroux, Parent-Boursier, & Mercier, 2014].…”
Section: Introductionmentioning
confidence: 99%